Community-Dwelling People Living With Dementia and Their Family Caregivers Experience Enhanced Relationships and Feelings of Well-Being Following Therapeutic Group Singing: A Qualitative Thematic Analysis - Clark, Imogen N.; Tamplin, Jeanette D.; Baker, Felicity A. (Frontiers in Psychology, 2018)
The progression of dementia can severely compromise interpersonal connection and relationship quality between people living with dementia (PwD) and their family caregivers (FCG), leading to social isolation and poor quality of life for both. Therapeutic group singing (TGS) is a socially engaging, stimulating, and supportive pursuit that community-dwelling PwD and their FCG can participate in together. This study aimed to build on the findings from previous research by undertaking a thematic analysis of interviews with 9 PwD (5 women, 4 men; mean age = 79.1 years) and 9 FCG (5 women, 4 men; mean age = 75.7 years). The interviews explored participants’ perspectives and experiences of a 20-week TGS intervention, underpinned by Kitwood’s model of person-centred care. Inductive thematic analysis resulted in the emergence of five themes which described how TGS for PwD and their FCG: 1) included supportive therapeutic facilitation and design features; 2) made group singing more accessible; 3) fostered new empathic friendships; 4) enhanced relationships between PwD and FCG; and 5) led to personal feelings of wellbeing for both PwD and FCG. Affinity with others who had similar life experiences and challenges created a sense of mutual understanding and camaraderie, which made group singing accessible without fear of judgement and social stigmas. For some PwD/FCG dyads, TGS meant they could continue a lifelong passion for singing together, while others enjoyed participating in singing together for the first time. Both PwD and FCG participants described personal feelings of acceptance, improved social confidence, mood, and purpose. Further, participants valued mental stimulation from TGS such as learning new skills and memory support. A model explaining relationships between themes suggests that TGS with person-centred facilitation features for PwD/FCG dyads led to affinity among group members with ripple effects, which enhanced accessibility to group singing, the formation of empathic friendships, PwD/FCG relationship quality, and personal wellbeing for both PwD and FCG. Psychoemotional, social and cognitive benefits from TGS described by participants in this study are known to promote self-identity, healthy relationships, and quality of life. This research highlights a need for improved availability of TGS for community-dwelling PwD/FCG dyads.